Synthesis Of Hematite/Mwcnts Nanocomposite Through Thermal Oxidation And Spin Coating - Abu Bakar, Noor Farah Iddayu (2019)
Recently, more research have been conducted towards decorating iron oxide with MWCNTs to form nanostructured materials. This is due to the unique amphoteric properties of iron oxide that offers the flexibility on shifting the surface charge of iron oxide as well as physicochemical properties obtained by MWCNTs. This iron oxides decorated with MWCNTs have shown photocatalytic, optical and visible light photoelectrochemical performance. This project has focused on the optimization of the growth process of α-Fe2O3 nanowires and decorated with MWCNTs to form α-Fe2O3/MWCNTs nanocomposite. This combination is then used for the photocatalysis application. Previously, iron oxide had limitation as photocatalyst because electron-hole charge recombination on the oxide surface and charge transportation as well as limitation in visible-light responsive. Hence, by combining with MWCNTs forming nanocomposite it would give the opportunity to extend the absorption wavelength of the UV light to visible light region and promote the generation and separation of photogenerated carrier in photocatalytic application. In this work, nanostructure was synthesized on Fe foil by oxidation process approach. Fe foil was used as substrate to grow the nanostructure. In order to get a good control of the dimension and high aspect ratio of the nanostructure, several parameter were investigated such as effect of oxidation temperature, time and condition on the substrate. The morphology and phase of α-Fe2O3 nanowires formed was characterized using FESEM, XRD and Raman. Under optimized oxidation condition (400 °C and 120 minutes), the length of nanowires are reached 1 - 1.8 μm and average nanostructure diameter is 40 - 70 nm. The density, length and diameter was found to be affected by the oxidation time and temperature. These factors influenced the rate of diffusion during oxidation thus will reflected the thickness of oxide layer. While, the composite sample of α-Fe2O3/MWCNTs nanocomposite were successfully formed by the spin coating of MWCNTs on the α-Fe2O3 nanostructure produced by optimized condition of 3500 rpm. The treatment of MWCNTs in 3 M HNO3 was conducted before spin coated on the α-Fe2O3 substrate to improve the solubility of MWCNTs in solvent. It was found that treated MWCNTs has shown better dispersion in DMF solvent. α-Fe2O3 nanostructure and α-Fe2O3/Fe2O3/MWCNTs were subjected to photocatalytic degradation using 30 ppm methyl orange for 5 hours of discoloration. Comparison studies in morphology and structure were performed between α-Fe2O3 thin film and α-Fe2O3/MWCNTs with different amount of MWCNTs to getting good interaction between α-Fe2O3 and MWCNTs. As the conclusion, α-Fe2O3/MWCNTs composite with 0.25 mg of MWCNTs was found to be more effective in the degradation of methyl orange compare to the bare α-Fe2O3 thin film.